The Influence of Principal Supervision and Organizational Culture Towards the Performance of Vocational Teachers - Linda Sukma; Yasir Arafat; Pahlawan Pahlawan (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of principal supervision and organizational culture on teacher performance within State Vocational Schools in Ogan Ilir Regency. Employing a quantitative descriptive method, data were collected via questionnaires from a sample of 67 teachers across five vocational schools. Statistical analysis included normality, linearity, and multicollinearity tests, followed by correlation, regression, t-tests, and an F-test. The results confirm that both principal supervision and organizational culture have a significant positive effect on teacher performance, with their combined influence explaining a substantial portion of the variance in performance outcomes. The novelty of this research lies in its focused examination of these two managerial factors within the specific context of Indonesian public vocational education, a sector critical to workforce development. A key practical implication is the need for district-level policies that train school principals in constructive supervision techniques while consciously fostering a collaborative and achievement-oriented school culture. This study contributes to the field of educational management by providing empirical evidence that strategic leadership and intentional cultural development are synergistic levers for enhancing teacher effectiveness in vocational settings.